HIV infection results in ventral–striatal reward system hypo-activation during cue processing. (17th July 2015) - Plessis, Stéfan du; Vink, Matthijs; Joska, John A.; Koutsilieri, Eleni; Bagadia, Asif; Stein, Dan J.; Emsley, Robin
Abstract : Objective: Functional MRI has thus far demonstrated that HIV has an impact on frontal–striatal systems involved in executive functioning. The potential impact of HIV on frontal–striatal systems involved in reward processing has yet to be examined by functional MRI. This study therefore aims to investigate the effects of HIV infection on reward processing by examining the function of the ventral–striatal reward system during a monetary incentive delay task. Design: This is a cross-sectional case-control study. Methods: Eighteen combined antiretroviral therapy-naive HIV-positive (HIV+) participants, as well as 16 matched healthy controls, performed a monetary incentive delay task. This paradigm assesses behaviour as well as functional brain activity-associated reward anticipation and reward outcome. Results: HIV+ participants showed a general decrease in activation associated with both neutral as well as potentially rewarding cues in their ventral striatum. We found normal activity related to reward outcome in the orbito-frontal cortex. Despite HIV+ participants' reaction times being significantly slower when independently measured from the reward paradigm, this performance deficit normalized during the performance of the reward task. Conclusion: HIV caused a decrease in activity during cue processing in the ventral striatum, with normal cortical functioning during reward outcome processing. Our results therefore suggest that HIV not only has an impact on fronto-striatal systems involved in executive functioning, but also has a direct impact on the function of the ventral–striatal reward system.